PENGARUH PRILAKU KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA GURU TAMAN KANAK-KANAK KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - -, Ermawati (Menara Ilmu, 2018)
This research aims to examine and analyze the influence of leadership behavior and workingsatisfaction toward teacher performance in Lareh Sago Halaban. The hypothesis of thisresearch are 1) the leadership has significant influence toward teacher performance, 2) workingsatisfaction has significant influence toward teacher performance, 3) the leadership andworking satisfaction have significant influence toward teacher performance.The sample of this research are 51 kindergarten teachers in Lare Sago Halaban. To examinethe relation and influence of dependent and independent variables, the date is analyzed byusing software SPSS.The result shows that the leadership behavior affects teacher performance, working satisfactionaffects teacher performance, and simultaneously the leadership behavior and workingsatisfaction affect teacher performance.This research support Herzberg’s theories (1990) and this discovery also give understandingabout the important role of leadership and working satisfaction toward teacher performance.Keywords: leadership, working satisfaction, performance